Anticancer Activity of Phanera semibifida Extract Evaluated by Brine Shrimp Lethality Test (BSLT) and Molecular Docking Studies - Meyla Suhendra; Berry Juliandi; Huda Shalahudin Darusman; Siti Sadiah; Fitmawati Fitmawati; Puji Rianti (Media Publikasi Cendekia Indonesia, 2026)
Indonesian people use plants as medicine because they are considered to have fewer side effects. The Lingga island community used Phanera semibifida (Roxb.) traditionally to make therapeutic drugs. P. semibifida has the potential to be a medicinal plant. We extracted stems and leaves with three different solvents and tested their cytotoxic activity. The ethanolic stem extract showed the highest value of LC₅₀ in the moderate toxicity category. The ethanolic steam extract continued to be subjected to in silico analysis, using molecular docking. We selected four compounds for molecular docking studies against five cancer-related proteins. The proteins are Estrogen receptor α, CDK2, Human Cytochrome P450 CYP17A1, Cyclin A, and BCL-2. The result showed that Ellagic acid bound strongly to Estrogen receptor α, CDK2, CYP17A1, and Cyclin A protein. Cyanidanol showed the highest affinity to BCL-2. These results suggest that P. semibifida contains compounds that can target multiple cancer-related proteins. Our findings highlight its potential as a source of anticancer agents. We recommend isolating these compounds and testing their efficacy through in vitro and in vivo studies to confirm their therapeutic potential in future studies.